Indications for inpatient treatment of cataract (Ukrainian Journal of Ophthalmology, 2026)
Purpose: To develop indications for inpatient cataract treatment based on the retrospective review of case histories of cataract patients.Materials and Methods: We retrospectively reviewed 636 case histories of cataract patients treated on an inpatient basis for at least two days. In addition, 20 experts working at Ukrainian tertiary care institutions responded to questions on potential causes of complications in cataract surgery, and their opinions were used to substantiate the indications for inpatient cataract treatment.Results: Hypertensive disease (HTD) and ischemic heart disease (IHD) were found in 34.6 ± 2.1% and 28.9 ± 2.0%, respectively, of the study patients. The presence of HTD and the presence of IHD in the cataract patient were associated with 1.8-times and 2.5-times, respectively, increased risk of postoperative complications when compared with patients without these comorbidities. The presence of glaucoma and the presence of mature cataract in the cataract patient were associated with 3.7-times and 1.8-times, respectively, increased risk of postoperative complications when compared with patients without these comorbidities.Inpatient treatment is in need in one-eyed cataract patients with very severe glaucoma and low vision or with mature cataracts, patients with bilateral mature cataracts, as well as cataract patients with lens subluxation, severe systemic disorders or mental disorders that prevent establishing productive contact with the patient.
Keywords: cataract; postoperative complications; systemic and ocular comorbidities